2011
DOI: 10.1007/s10549-011-1824-4
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of the tumor suppressor klotho in human breast cancer

Abstract: Klotho is a single pass transmembrane protein, associated with premature aging. We identified tumor suppressor activities for klotho, associated with reduced expression in breast cancer. We now aimed to analyze klotho expression in early stages of breast tumorigenesis and elucidate mechanisms leading to klotho silencing in breast tumors. We studied klotho expression, using immunohistochemistry, and found high klotho expression in all normal and mild hyperplasia samples, whereas reduced expression was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 32 publications
5
79
1
4
Order By: Relevance
“…In CKD, accumulated indoxyl sulfate or p-cresyl sulfate in the blood induces hypermethylation of the Klotho gene and decreased Klotho expression in CKD [81,82] . The hyperacetylation of histone in the Klotho promoter also inhibits Klotho expression [83] . TNF and TNF-like weak inducer of apoptosis-downregulated renal Klotho expression can be blunted by inhibition of histone deacetylase [84] , indicating that cytokine-induced elevation of histone acetylation is associated with downregulation of Klotho expression.…”
Section: Replacement Of Klothomentioning
confidence: 99%
“…In CKD, accumulated indoxyl sulfate or p-cresyl sulfate in the blood induces hypermethylation of the Klotho gene and decreased Klotho expression in CKD [81,82] . The hyperacetylation of histone in the Klotho promoter also inhibits Klotho expression [83] . TNF and TNF-like weak inducer of apoptosis-downregulated renal Klotho expression can be blunted by inhibition of histone deacetylase [84] , indicating that cytokine-induced elevation of histone acetylation is associated with downregulation of Klotho expression.…”
Section: Replacement Of Klothomentioning
confidence: 99%
“…We have previously shown that klotho is abundantly expressed in normal breast and pancreatic tissues and that upon malignant transformation its expression is reduced (9,10,17). Restoring klotho expression, or treatment with the soluble protein, inhibited proliferation of breast and pancreatic cancer cells (9,10), and further studies indicated it as an inhibitor of the IGF-1 pathway (4,9).…”
Section: Introductionmentioning
confidence: 98%
“…This phenomenon has been suggested to underlie the tightly controlled tissue-specific pattern of α-Klotho expression (Azuma et al, 2012) and is reported to increase with age (King et al, 2012). Interestingly, increased KL promoter methylation has also been described in a number of cancers, including cervical carcinoma, colorectal, breast and gastric cancers Pan et al, 2011;Rubinek et al, 2012;Wang et al, 2011). Fascinatingly, promoter methylation may be important to our observations.…”
Section: How Does Kidney Damage Cause Loss Of α-Klotho In the Brain? mentioning
confidence: 53%